2001
DOI: 10.1159/000056089
|View full text |Cite
|
Sign up to set email alerts
|

Central Serotonergic Mechanisms on Head Twitch Response Induced by Benzodiazepine Receptor Agonists

Abstract: Intraperitoneal injection of benzodiazepine receptor agonists (estazolam, zopiclone, triazolam: 0.03–0.24 mmol/kg) induces the head twitch response (HTR). The present study was undertaken to examine the possible participation of the serotonergic system in the mechanism of head twitches induced by benzodiazepine receptor agonists (BZ-RAs). The HTR induced by BZ-RAs was suppressed by pretreatment with ketanserine (1 mg/kg, i.p.), a selective 5-HT2 receptor antagonist. Pretreatment with fluoxetine (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, we have shown previously that PKCγ regulates ethanol-stimulated GABA A receptor function in cortex (Harris et al, 1995). It has been shown that GABAergic drugs modulate head twitch behavior in rodents, perhaps through interaction with 5-HT 2 receptors (Handley and Singh, 1985;Moser and Redfern, 1988;Tadano et al, 2001). Feng et al (2001) reported that activation of 5-HT 2 receptors in the prefrontal cortex of rats increased in vitro PKC activity toward GABA A receptor γ 2 subunits.…”
Section: Behavioral Assessments Of 5ht 2a/c Receptorsmentioning
confidence: 97%
“…For example, we have shown previously that PKCγ regulates ethanol-stimulated GABA A receptor function in cortex (Harris et al, 1995). It has been shown that GABAergic drugs modulate head twitch behavior in rodents, perhaps through interaction with 5-HT 2 receptors (Handley and Singh, 1985;Moser and Redfern, 1988;Tadano et al, 2001). Feng et al (2001) reported that activation of 5-HT 2 receptors in the prefrontal cortex of rats increased in vitro PKC activity toward GABA A receptor γ 2 subunits.…”
Section: Behavioral Assessments Of 5ht 2a/c Receptorsmentioning
confidence: 97%
“…Nevertheless, there is little evidence to support using the HTR as an animal model of hallucinations or of mental states that are directly relevant to schizophrenia. For example, many non-hallucinogenic compounds that increase 5-HT release and indirectly activate the 5-HT 2A receptor, including d-fenfluramine (Darmani, 1997) and even some benzodiazepines (Tadano et al, 2001), can induce the HTR. Furthermore, although many antipsychotics can block the hallucinogen-induced HTR due to their 5-HT 2A antagonist activity, selective 5-HT 2A antagonists such as M100,907 have only limited efficacy as antipsychotics when administered to schizophrenia patients.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, selective 5-HT 2A antagonists block the HTR induced by DOI and other hallucinogens (Schreiber et al, 1995; Fantegrossi et al, 2005, 2006, 2008, 2010), and hallucinogens do not induce the HTR in 5-HT 2A knockout mice (Gonzalez-Maeso et al, 2003, 2007; Keiser et al, 2009; Halberstadt et al, 2011). Although phencyclidine (Nabeshima et al, 1987), benzodiazepines (Tadano et al, 2001), the CB 1 antagonist SR 14176A (Darmani and Pandya, 2000), the 5-HT 1A antagonist WAY-100635 (Darmani, 1998), and thyrotropin-releasing hormone analogs (Fone et al, 1989) induce the HTR, these effects are blocked by 5-HT 2A receptor antagonists. Because of this specificity, this behavior has been widely adopted as an animal behavioral assay for 5-HT 2A activation and hallucinogen-like effects.…”
mentioning
confidence: 99%